Permanência na graduação a distância na perspectiva dos estudantes : um estudo a partir da experiência do projeto Alfa Guia - Santos, Pricila Kohls dos (2015)
School dropout represents, at the same time, a complex and necessary issue for the quality of actions to students’ permanency at higher education, taking into account this education sector's expansion and therefore eminent challenges which follows such university expansion. Course offerings in the distance education modality are considered high when compared with classroom courses and it is impacting the expected result of the academic formation, especially in regard to teacher training. Thus, to know the reasons because students abandon their studies represents the first step to qualification of the actions to students’ permanency and retention. The search for indicators and tools which allow understanding what makes a student stand is a challenge. Using as theoretical background the work of Tinto (1989, 1997, 2006), Garland (1993), Kember (1995), Aretio (2002), Cabrera (2006), Castles (2004), Tello (2007) and from the author experience with Project Alfa GUIA, it was carried out a study about the quali-quantitative character to verify whether the investigation tool used by Project Alfa GUIA could be adapted to offer these indicators, since the data related to distance education available in Brazilian system is fragile. As a result of this investigation, we observed that the original tool did not contemplate all items required, especially about the influence of virtual environment, considering that it is the place where interactions and practices are consolidated. However, there are indicators showing that the structure proposed in this dissertation has potential to select the information that support to understand the student who stands’ perspective. We describe some indicators and also additional issues to be explored, in order that we can measure the typical nuances of this modality, and contributing with teachers and students for courses project's building, which contemplate aspects that support to mitigate this serious problem of high social cost.